Penerapan Metode Simple Additive Weighting (SAW) Dalam Sistem Pendukung Keputusan Pemilihan Kapal Sebagai Moda Transportasi Laut - Zainal Arifin, Muhammad; Suharjo ST, M.Eng., MCF., Imam (Fakultas Teknik Universitas Hamzanwadi, 2024)
Maritime transportation has become the primary choice for Indonesian society due to its ability to carry passengers and goods in large quantities at relatively low costs. Based on data from the Indonesian Ministry of Transportation, there are 306 ships operating in domestic crossings, with 118 managed by ASDP Ferry Indonesia, 170 private ships, and 18 BUMF ships. Based on deep learning, this study aims to assist students of the Selaparang Lombok Yogyakarta dormitory in recommending the best ship selection for the Surabaya-Lombok route and vice versa. The decision support system is evaluated based on criteria including ticket prices, travel time, travel comfort, facilities, ship capacity, safety, departure schedule regularity, and operator reputation. This study uses a simple Weighted Evaluation Method called Simple Additive Weighting to determine the best alternative ranking. The results show that the comparison test between the system calculation and Microsoft Excel calculation results in 100% similarity. KMP Kirana VII occupies the first rank with a value of 0.95, making it the best ship solution suitable for student use